Nitrogen-Doped Carbons in Li–S Batteries: Materials Design and Electrochemical Mechanism - Li, Xia; Sun, Xueliang (Frontiers in Energy Research, 2014)
Li-S batteries have been considered as next generation Li batteries due to their high theoretical energy density. Over the past few years, researchers have made significant efforts in breaking through critical bottlenecks which impede the commercialization of Li-S batteries. Beginning with a basic introduction to Li-S systems and their associated mechanism, this review will highlight the application of one specific carbon family, nitrogen-doped carbon materials in sulfur based cathodes. These materials will include nitrogen doped porous carbon, carbon nanotubes, nanofibers and graphene. The article will conclude with a summary of recent research efforts in this field as well as the future prospects for the use of nitrogen-doped carbon materials in Li-S batteries.